2014
DOI: 10.1002/lary.24979
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of the eustachian tube lumen with Valsalva computed tomography

Abstract: Valsalva CT consistently allows visualization of the lumen of the distal one-third of the eustachian tube in a majority of patients with no eustachian tube-related complaints. This technique might be helpful in localizing eustachian tube pathology in patients with obstructive tube symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 18 publications
2
34
0
2
Order By: Relevance
“…We recently described Valsalva CT as a way to identify distal obstruction; in the great majority of the normal population, the distal one-third of the Eustachian tube can be visualized and the patency of that segment of the Eustachian tube can be assured. 8 In our study population of patients undergoing surgery for chronic ear disease, only two ears had a distal obstruction, which is similar to the frequency expected in the general population.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We recently described Valsalva CT as a way to identify distal obstruction; in the great majority of the normal population, the distal one-third of the Eustachian tube can be visualized and the patency of that segment of the Eustachian tube can be assured. 8 In our study population of patients undergoing surgery for chronic ear disease, only two ears had a distal obstruction, which is similar to the frequency expected in the general population.…”
Section: Discussionsupporting
confidence: 83%
“…Endoscopic ear surgery with rigid angled scopes allows for high‐resolution evaluation of the protympanic segment of the tube . Valsalva computed tomography (CT) has been recently reported by our group as a method for visualizing the lumen of the distal one‐third of the Eustachian tube . We have utilized both modalities to evaluate any identifiable anatomic obstruction in the Eustachian tube in patients undergoing ear surgery for chronic disease in our practice.…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative computed tomography (CT) was used for calibration and visualization of the cartilaginous portion of ET [13]. High-resolution paranasal CT scans were conducted using a GMS Revolution CT scanner (GE Healthcare, Milwaukee, WI, USA) with the patients in supine position, with and without Valsalva maneuver.…”
Section: Preoperative Computed Tomography Scan Protocolmentioning
confidence: 99%
“…Tóth et al [5] showed that the main structure of the protympanum develops from the petrous part of the temporal bone while the tympanic part forms the posterior border of the protympanum laterally. It is also the location of the narrowest portion of the Eustachian tube, the isthmus [6, 7]. …”
Section: Introductionmentioning
confidence: 99%